Using Brain-Computer Interface to evaluate the User eXperience in interactive systems - Cano, Sandra (2022)
Electroencephalography is a technique, which allows to capture brain activity. Devices BCI (Brain-Computer Interface) are being used to evaluate the UX (User eXperience). We present a study where was designed an experiment using the OPENBCI device. The experiment consisted of capturing the brain activity to analyse the data of a group of people (women; men) when they interacted with a classic game called Snake. Therefore, the study designed two interaction ways. First interaction involved a traditional interaction with computer and keyboard. The second interaction involve the use of NFC cards and a mobile device. Also, were applied questionnaires, such as: SAM (Self-Assessment Manikin), NASA-TLX and SUS (System Usability Scale), to compare the information recollected through of the BCI, which consistency with the data was reflected.